Wilson’s Disease: An Update on the Diagnostic Workup and Management - Beata Kasztelan-Szczerbinska (MDPI AG, 2021)
Wilson’s disease (WD) is a rare autosomal recessive disorder of hepatocellular copper deposition. The diagnostic approach to patients with WD may be challenging and is based on a complex set of clinical findings that derive from patient history, physical examination, as well as laboratory and imaging testing. No single examination can unequivocally confirm or exclude the disease. Timely identification of signs and symptoms using novel biomarkers and modern diagnostic tools may help to reduce treatment delays and improve patient prognosis. The proper way of approaching WD management includes, firstly, early diagnosis and prompt treatment introduction; secondly, careful and lifelong monitoring of patient compliance and strict adherence to the treatment; and, last but not least, screening for adverse effects and evaluation of treatment efficacy. Liver transplantation is performed in about 5% of WD patients who present with acute liver failure at first disease presentation or with signs of decompensation in the course of liver cirrhosis. Increasing awareness of this rare inherited disease among health professionals, emphasizing their training to consider early signs and symptoms of the illness, and strict monitoring are vital strategies for the patient safety and efficacy of WD therapy.